Western Union Telegram to Jane Tolmach from William Connell - William Connell:::::: (1968)
A Western Union telegram from the White House that invites Mrs. Jane Tolmach to attend a closed breakfast with the Vice President and other Democratic leaders. The event is scheduled for January 13 at 8:30 a.m. in the Riesling Room of the Del Webb Town House Hotel in Fresno, California. The telegram requests that she RSVP to Arlene Hudson and is signed by William Connell, Executive Assistant.